The Influence of As-Sa'ah Media on Improving Students' Understanding of 'Adad Tartibi in Grade VIII at MTs Ishlahul Amanah - Devia, Rahma; Nursyamsiah, Nunung; Khalid, Shofa Musthofa (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The current development of Arabic language learning in Indonesia is still not optimal, because there are still many obstacles that have to faced especially by students in its implementation. The study examines the impact of